Use of Services by People Living Alone With Cognitive Impairment: A Systematic Review. Issue 1 (18th January 2021) - Rosenwohl-Mack, Amy; Dubbin, Leslie; Chodos, Anna; Dulaney, Sarah; Fang, Min-Lin; Merrilees, Jennifer; Portacolone, Elena
Abstract: Background and Objectives: Formal supports and social services are essential to people living alone with cognitive impairment (PLACI) because they are at risk of negative health outcomes and lack cohabitants who may support them with cognitively demanding tasks. To further our understanding of this critical and worldwide issue, we conducted a systematic review to understand whether, and how, PLACI access and use essential formal supports and services. Research Design and Methods: We searched 6 databases (PubMed, Embase, PsycINFO, CINAHL, Web of Science, and Sociological Abstracts) to identify quantitative and mixed-method literature on formal service use among PLACI. The initial search was conducted in 2018 and updated in 2020. Results: We identified 32 studies published between 1992 and 2019, representing 13 countries, that met our criteria: 16 reported on health services and 26 on social services. Most studies compared PLACI with people with cognitive impairment living with others. Health service use was lower or similar among PLACI, as opposed to counterparts living with others. Most studies reported a higher use of social services (e.g., home services) among PLACI than those living with others. Overall use of essential home service among PLACI was higher in Europe than in the United States, a country where large portions of PLACI were reported receiving no formal services. Discussion and Implications: We identified wide variability among countries and major gaps in service use. Results for use of health services were mixed, although our findings suggest that PLACI may have fewer physician visits than counterparts living with others. Our findings suggest that varying policies and budgets for these services among countries may have affected our findings. We encourage researchers to evaluate and compare the influence of social policies in the well-being of PLACI. We also encourage policy makers to prioritize the needs of PLACI in national dementia strategies.